The plasma fibrinogen levels in the nitroglycerin-induced chronic migraine rat model and its association between migraine-associated vestibular dysfunction - Zhang, Jilei; Zhao, Yixin; Jing, Yuanyuan; Han, Lin; Ma, Xin; Yu, Lisheng; Diao, Tongxiang (Frontiers in Neurology, 2023)
The purpose of this study was to measure the vestibular function and plasma fibrinogen level in the nitroglycerin (NTG)-induced chronic migraine rats, and explore the effect of defibrinogenation on migraine and associated vestibular dysfunction. The chronic migraine rat model was built by recurrent NTG injection. Batroxobin was administrated as a defibrinogenating drug. We measured the mechanical withdrawal threshold, vestibular function, and fibrinogen level of the rats 30 min before and 2 h following the model establishment, as well as 1 h after batroxobin administration. The results showed that vestibular function was impaired in NTG-induced chronic migraine rats. The fibrinogen levels were increased following repeated NTG injections. However, defibrinogenation did not affect either aggravating or alleviating mechanical hyperalgesia or vestibular dysfunction in the migraine model rats. These findings suggest that the NTG-induced chronic migraine rat model can be used for research on migraine-associated vestibular symptoms. Albeit the association between elevated fibrinogen levels and migraine attacks can be observed, the role of excessive fibrinogen in the pathogenesis of chronic migraine is yet to be determined.